Sosialisasi Penerapan Protokol Kesehatan Berstandar CHSE untuk Receptionist Restoran dan Concierge Hotel dalam Menunjang Pariwisata di Kota Bogor - Maidar Simanihuruk; Yuviani Kusumawardhani; Dina Mayasari; Sekti Rahardjo (ACADEMICS IN ACTION Journal of Community Empowerment, 2022)
It is essential to use Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) in restaurants and hotels to support tourism in the new normal era. It is anticipated to help the community by raising awareness of the importance of cleanliness, health, safety, and environmental sustainability through socialization of the implementation of the CHSE protocol. So that hotel owners or employees are highly aware of and interested in it, and the restaurant is primarily about environmental cleanliness in order to achieve the go-green goal. The goal of this socialization is to prepare employees, guests, suppliers, vendors, contractors, and other hotel and restaurant stakeholders to return to Bogor for guest visits. The method of implementing health protocol socialization with CHSE standards () was carried out through technical guidance to employees of the restaurant receptionist and hotel concierge divisions in Bogor City, with methods of lecturing, tutorials, discussions, games, and evaluations to as many as 30 participants. The average value of participants' understanding of the CHSE aspects was 88.86 percent, indicating that all participants understood what indicators were included in the CHSE aspects, according to the results of this puzzle game.